(untitled) (Veterinary Science, 2017)
Botulism is a neuroparalytic affection caused by ingestion of toxins produced by Clostridium botulinum, a gram positive bacterium, anaerobic spore-forming, which are widely distributed in nature, soil and sediments of lakes and seas. It has been described seven neurotoxins (A to G); the C most commonly found in small animals. In dogs, the disease mainly occurs by ingestion of preformed toxin present in spoiled food or rotting carcasses. The neurotoxin type C cause blockage of acetylcholine receptors at neuromuscular junction, generally from hours to days after ingestion. The affected dogs have ascending flaccid paralysis of the skeletal muscles, although the sensitivity and awareness are maintained. Initial diagnosis is carried out through the history of the animal as well as clinical manifestations. The standard technique for definitive diagnosis is intraperitoneal inoculation of blood serum of suspected animals in mice. Supportive care is essential to recovery. The prognosis is good if there is no development of secondary infections or other complications. The recovery is complete after a period of 2 to 3 weeks. In more severe cases, death can occur due to paralysis of the respiratory muscles. The prevention of the disease in dogs is based on restricting the consumption of spoiled food or rotting carcasses